Effect of Burning and Tillage Options on Yields in a Continuous Wheat-Double-Crop Soybean Rotation - D. W. Sweeney; D. R. Presley; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2021)
Double-cropping soybeans after wheat is common in southeastern Kansas and yields of double-crop soybean during the three years of this study were not affected by management of previous wheat straw practices such as burning or tillage done before planting. However, in the second and third year of the study, subsequent wheat yields were increased by 30% or more when the wheat residue had been burned the previous year.
Keywords: Double-crop; soybean; wheat residue; burn; tillage